Looking at the Self-innovation and Learning Models for the Internship Program Students during the Covid-19 Pandemic: A Qualitative Study - Sofyan Sofyan; Robin Pratama (Universitas Jambi, Indonesia, 2022)
This research explored the impact of the Covid 19 pandemic on the ability of self-innovation and adjustment of learning models for students. It focused on the internship program at one education program, in a public university in Jambi. Based on the research problems and objectives, this research used a generic qualitative approach. It explored the structure of consciousness as experienced from the first-person point of view. The central system of an experience is its intentionality, which is directed at something because it is an experience or about some object. An experience is required for an object based on its content or meaning (representing the object) along with the appropriate enabling conditions.